2013
DOI: 10.1186/scrt170
|View full text |Cite
|
Sign up to set email alerts
|

The uncertain role of unmodified mesenchymal stem cells in tumor progression: what master switch?

Abstract: Mesenchymal stem cells (MSCs) are emerging as promising gene vectors for cancer therapy because of their unique characteristics, including the ease of their expansion and genetic modification and their remarkable tumor-tropic properties. However, there remains a concern that MSCs may promote cancer progression. Surprisingly, there are conflicting reports within the literature describing both the promotion and inhibition of cancer progression by MSCs. The reasons for this discrepancy are still unknown. The surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
0
24
1
Order By: Relevance
“…MSCs have been most commonly applied clinically in adoptive cell therapy approaches based on their potent regenerative capacity . Despite some controversy on the role of MSCs in tumor setting, it is believed that these cells may support tumor progression by suppressing the host immune response . Inadequate evidence on T cell inhibition by tumor conditioned MSCs prompted us to explore the role of TC‐MSCs on DC/T cell function(s) in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have been most commonly applied clinically in adoptive cell therapy approaches based on their potent regenerative capacity . Despite some controversy on the role of MSCs in tumor setting, it is believed that these cells may support tumor progression by suppressing the host immune response . Inadequate evidence on T cell inhibition by tumor conditioned MSCs prompted us to explore the role of TC‐MSCs on DC/T cell function(s) in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…38 Despite some controversy on the role of MSCs in tumor setting, 38 it is believed that these cells may support tumor progression by suppressing the host immune response. 39,40 Inadequate evidence on T cell inhibition by tumor conditioned MSCs prompted us to explore the role of TC-MSCs on DC/T cell function(s) in vitro. We report the following novel observations: first, TC-MSCs suppress proliferation and late phase effector functions (IFNg secretion and tumor cell cytotoxicity) of T cells without affecting their early activation; second, TC-MSC mediated suppression of T cell proliferation is contact independent and mediated by TC-MSC-produced IL-10; third, this IL-10 represses cystathionase gene expression in DCs and thereby inhibits DC export of cysteine required by cognate T cells for their optimal proliferation; and finally, pSTAT3 may directly bind with a GAS motif present within the cystathionase promoter of DC after IL-10 stimulation, leading to repression of cystathionase transcription.…”
Section: Discussionmentioning
confidence: 99%
“…However, Liyang et al . reported that CD133‐positive MSCs can be isolated from UCB . They had high proliferative potential and were passaged every 5–6 days.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can affect many cancer hallmarks such as angiogenesis, metastasis, antiapoptosis, and evasion of the immune system. 2,13,21,22,34,35 The presence, route, and effects of endogenously circulating MSCs, however, have not been intensively studied. According to some, they are difficult (if not impossible) to detect.…”
Section: Discussionmentioning
confidence: 99%